2020
DOI: 10.1002/ejoc.202000142
|View full text |Cite
|
Sign up to set email alerts
|

Metal Free, Direct and Selective Deoxygenation of α‐Hydroxy Carbonyl Compounds: Access to α,α‐Diaryl Carbonyl Compounds

Abstract: An efficient, metal free, direct and selective deoxygenation of α-hydroxy carbonyl compounds is achieved with the aid of catalytic amount of aqueous HClO 4 (70 %) and triethylsilane as hydride source. A variety of α-hydroxy-α,α-diaryl carbonyl compounds are selectively deoxygenated to give α,α-[a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…With the increasing demand for chemical sustainability and friendliness, developing a metal-free and recyclable catalytic system is becoming more attractive to reduce the use of toxic and expensive metals and benefits environmental compatibility, high efficiency, and so on. To date, only several metal-free catalytic systems for direct deoxygenation of alcohols have been explored in halogen or supercritical media (Scheme c). However, toxic halogens and harsh conditions prevented these systems from being widely used. In addition, our group developed TsOH·H 2 O as the Brønsted acid catalyst for direct reduction of aromatic allylic alcohols in toluene recently, providing up to 94% yield .…”
Section: Introductionsupporting
confidence: 58%
“…With the increasing demand for chemical sustainability and friendliness, developing a metal-free and recyclable catalytic system is becoming more attractive to reduce the use of toxic and expensive metals and benefits environmental compatibility, high efficiency, and so on. To date, only several metal-free catalytic systems for direct deoxygenation of alcohols have been explored in halogen or supercritical media (Scheme c). However, toxic halogens and harsh conditions prevented these systems from being widely used. In addition, our group developed TsOH·H 2 O as the Brønsted acid catalyst for direct reduction of aromatic allylic alcohols in toluene recently, providing up to 94% yield .…”
Section: Introductionsupporting
confidence: 58%
“…[27][28][29][30][31][32][33] In the past decade or so, tertiary α-hydroxy ketones have also been utilized as versatile building blocks to access biologically active scaffolds of heterocycles and α-functionalized ketones. [34][35][36][37][38][39][40] Analyses of the existence of conformational preferences (if any) among tertiary α-hydroxy ketone moieties may show some light on their mode of action (based on molecular topology) that leads to biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, α-functionalization through α-carbonyl cations has recently emerged as an alternative to the enolate chemistry. Several synthetic strategies involving α-carbonyl cations have been developed in the past decade to achieve the α-functionalization of a wide variety of carbonyl compounds. In all such conversions, though the intermediacy of α-carbonyl cations was proposed unequivocally, no favorable attempts could be made to capture and detect those elusive intermediates directly (Supplementary Note 1). α-Carbonyl cations are generally regarded as destabilized carbocations due to the presence of the electron-withdrawing carbonyl group at the cationic center. , Owing to its high reactivity toward the nucleophile or rapid molecular rearrangement, intercepting and detecting an intrinsically unstable α-carbonyl cation from an ongoing reaction poses a challenging task.…”
mentioning
confidence: 99%
“…We investigated the possible intermediacy of α-carbonyl cation in three model reactions: Friedel–Crafts arylation, deoxygenation, and azidation of α-hydroxy carbonyl compounds (Figure ). Based on substrate and product studies, literature precedence suggested the cleavage of the C–OH bond of the α-hydroxy carbonyl compound, forming the α-carbonyl cation as the key intermediate in mechanistic pathways of these reactions (Figure ).…”
mentioning
confidence: 99%
See 1 more Smart Citation